2016
DOI: 10.1172/jci85794
|View full text |Cite
|
Sign up to set email alerts
|

EPHB4 kinase–inactivating mutations cause autosomal dominant lymphatic-related hydrops fetalis

Abstract: Hydrops fetalis describes fluid accumulation in at least 2 fetal compartments, including abdominal cavities, pleura, and pericardium, or in body tissue. The majority of hydrops fetalis cases are nonimmune conditions that present with generalized edema of the fetus, and approximately 15% of these nonimmune cases result from a lymphatic abnormality. Here, we have identified an autosomal dominant, inherited form of lymphatic-related (nonimmune) hydrops fetalis (LRHF). Independent exome sequencing projects on 2 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 37 publications
1
118
0
Order By: Relevance
“…Some patients may develop severe non-immune lymphatic-related hydrops fetalis in utero, resulting in early death, whereas others may have milder manifestations, such as atrial septal defect or varicose veins as adults. The hydrops and swelling improve spontaneously in those who survive the neonatal period 39. Martin-Almedina et al 39 found two different heterozygous missense mutations in EPHB4 (OMIM: 600011) in 11 patients with HFASD from two unrelated families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients may develop severe non-immune lymphatic-related hydrops fetalis in utero, resulting in early death, whereas others may have milder manifestations, such as atrial septal defect or varicose veins as adults. The hydrops and swelling improve spontaneously in those who survive the neonatal period 39. Martin-Almedina et al 39 found two different heterozygous missense mutations in EPHB4 (OMIM: 600011) in 11 patients with HFASD from two unrelated families.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrops and swelling improve spontaneously in those who survive the neonatal period 39. Martin-Almedina et al 39 found two different heterozygous missense mutations in EPHB4 (OMIM: 600011) in 11 patients with HFASD from two unrelated families. The mutations, which were found by whole-exome sequencing, segregated with the disorder, although there was variable expressivity of the phenotype 39…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of Ephb4 in LECs leads to defective lymphovenous valve formation and consequent subcutaneous edema (655). As a main component of the valve, ECM also plays an important role in the lymphovenous valve formation.…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…7 There was a high incidence of atrial septal defects in these families. EPHB4 was found to be an important regulator of early lymphatic vascular development and mutations in the gene can cause an autosomal dominant form of non-immune hydrops with variable expressivity, but associated with high mortality rate.…”
Section: Ephb4-related Lymphatic-related Hydropsmentioning
confidence: 96%
“…Since then, two new genes -PIEZO1 and EPHB4 -have been identified as a cause of generalised lymphatic dysplasia 6,7 and the overgrowth/vascular malformation syndromes are now collectively known as the PIK3CA -related overgrowth spectrum (PROS) disorders because they are caused by somatic mutations in the phosphatidylinositol-3-kinase (PI3K)/AKT/mTOR pathway. 8 An adapted classification system is presented in Fig 2 . A summary of the features and presentations of some of the conditions can be found in Table 1 .…”
Section: Key Pointsmentioning
confidence: 99%